Bevacizumab Plus FOLFOX-4 Combined With Deep Electro-Hyperthermia as First-line Therapy in Metastatic Colon Cancer: A Pilot Study - Ranieri, Girolamo; Laface, Carmelo; Laforgia, Mariarita; De Summa, Simona; Porcelli, Mariangela; Macina, Francesco; Ammendola, Michele; Molinari, Pasquale; Lauletta, Gianfranco; Di Palo, Alessandra; Rubini, Giuseppe; Ferrari, Cristina; et al. (Frontiers in Oncology, 2020)
Bevacizumab plus FOLFOX-4 regimen represents the first-line therapy in patients affected by metastatic colorectal cancer (mCRC). Hyperthermia has been considered an effective ancillary treatment for cancer therapy through several anti-tumour mechanisms, sharing with Bevacizumab the inhibition of angiogenesis. Up to now, scientific literature offers very few clinical data on the combination of bevacizumab plus oxaliplatin-based chemotherapy with deep electro-hyperthermia (DEHY) for metastatic colon cancer (mCC) patients. Therefore, we aimed at evaluating the efficacy of this combination based on the possible interaction between the DEHY and Bevacizumab anti-tumour mechanisms. We conducted a retrospective analysis on 40 patients affected by mCC treated with the combination of Bevacizumab plus FOLFOX-4 (fluorouracil/folinic acid plus oxaliplatin) and DEHY (EHY2000), between January 2017 and May 2020. DEHY treatment was performed weekly, with capacitive electrodes at 80-110W for 50 min, during and between subsequent bevacizumab administrations, on abdomen for liver or abdominal lymph nodes metastases and thorax for lung metastases. Treatment response assessment was performed, according to the Response Evaluation Criteria for Solid Tumors (RECIST). The primary endpoints were disease control rate (DCR) and progression-free survival (PFS). The secondary endpoint was overall survival (OS). DCR, counted as the percentage of patients who had the best response rating [complete response (CR), partial response (PR), or stable disease (SD)], was assessed at 90 days (timepoint-1) and at 180 days (timepoint-2). DCR was 95% and 89,5% at timepoint-1 and timepoint-2, respectively. The median PFS was 12,1 months, whereas the median OS was 21,4 months. No major toxicity related to DEHY was registered; overall, this combination regimen was safe. Our results suggest that the combined treatment of DEHY with Bevacizumab plus FOLFOX-4 as first-line therapy in mCC is feasible and effective with a favourable disease control, prolonging PFS of 2,7 months with respect to standard treatment without DEHY for mCC patients. Further studies will be required to prove its merit and explore its potentiality, especially if compared to conventional treatment.